The development of human capital in Ukraine: global influences and tendencies - Smirnova, І.; Simakov, K. (Економічний вісник Донбасу, 2018)
The problems of development of human capital are considered and the preconditions for ensuring its competitiveness in Ukraine are determined. The position of the country in the index of global competitiveness and human capital and its components is investigated. It is determined that the indicator of efficiency of human capital exploitation in Ukraine is the lowest because of the lack of a system of commercialization of technologies. The reasons for the outflow of human capital from Ukraine to the EU countries are determined and ways of overcoming the emigration are proposed. It is proved that in order to ensure the quality of human capital and intensify investment in its development in Ukraine it is necessary to promote the process of innovation development in educational institutions, supplemented by its introduction of innovative technologies in the field of higher education; provide training in accordance with the modern requirements of employers for their mobility, the ability to generate new ideas and readiness to innovate within the strategic objectives of the enterprise. Розглянуто проблеми розвитку людського капіталу та визначено передумов забезпечення його конкурентоспроможності в Україні. Досліджено позиції країни в індексі глобальної конкурентоспроможності та людського капіталу і його складових. Визначено, що показник ефективності експлуатації людського капіталу в Україні є найнижчим через відсутність системи комерціалізації технологій. З'ясовано причини відтоку людського капіталу з України до країн ЄС та запропоновано шляхи подолання еміграції. Доведено, що для забезпечення якості людського капіталу та активізації інвестицій у його розвиток в Україні необхідно сприяти стимулюванню процесу інноваційного розвитку в навчальних закладах, доповнивши його впровадженням інноваційних технологій у галузі одержання вищої освіти; забезпечити підготовку кадрів відповідно до сучасних вимог роботодавців за їхньою мобільністю, можливості генерувати нові ідеї та готовність до реалізації інновацій в рамках стратегічних цілей підприємства. Рассмотрены проблемы развития человеческого капитала и определены предпосылки обеспечения его конкурентоспособности в Украине. Исследованы позиции страны в индексе глобальной конкурентоспособности и человеческого капитала и его составляющих. Определено, что показатель эффективности эксплуатации человеческого капитала в Украине является наиболее низким из-за отсутствия системы коммерциализации технологий. Установлены причины оттока человеческого капитала из Украины в страны ЕС и предложены пути преодоления эмиграции. Доказано, что для обеспечения качества человеческого капитала и активизации инвестиций в его развитие в Украине, необходимо оказывать содействие стимулированию процесса инновационного развития в учебных заведениях, дополнив его внедрением инновационных технологий в области получения высшего образования; обеспечить подготовку кадров согласно современным требованиям работодателей по их мобильности, возможности генерировать новые идеи и готовность к реализации инноваций в рамках стратегических целей предприятий.